Exploring Causes of Low English Proficiency Among Burundian Undergraduates Despite Novel Teaching - Déogratias Butoyi; Audace Mbonyingingo; Christopher Joseph Odhiambo (Yayasan Visi Intan Permata, 2026)
English serves as a lingua franca, making high proficiency essential for effective communication across the world. Consequently, numerous studies have been carried out in EFL academic settings to identify and fight causes of low proficiency in English. However, the specific role of the novel in boosting language competence has received little attention or no attention at all, especially at a university in Burundi. Poor proficiency is evident among students in the English Section of Burundi Higher Institute of Education (ENS) and the English Department of the Institute of Applied Pedagogy (IPA, University of Burundi), despite frequent exposure to lectures on the novel in English. This study aimed to investigate how novels are actually used in these institutions, deduce the underlying causes of students' linguistic incompetence, and propose effective solutions to the research problem. A qualitative research design was employed. A semi-structured, face-to-face interview was conducted with 20 students (half of them from ENS, the other half from IPA) and five literature lecturers (three from ENS and two from IPA) during the academic year 2022-2023. The researcher transcribed textually the recorded voices of both categories of interviewees and analyzed the data using the